Sustainable territorial development: knowledge put into value under an innovation ecosystem approach - Contreras Varas, Juan Carlos (2024)
The article presented here proposes a dialectical, systemic and virtuous relationship and approach between the territory and innovation, considering the different types of existing knowledge as essential inputs to be used to contribute to local development. The efforts in its application will be oriented to the strengthening of the capacities of the social actors and the identification and subsequent deployment of the processes that will enable and occupy the resources to achieve a systematic and systemic advance of the territories as their own realities, with sufficient muscle to value the experiences, traditions, histories, attributes and knowledge. The aforementioned makes possible the formation and transformation of social actors, in protagonists of the design of a new territorial situation, which raises the need to solve the central knots of society, consistently with building a territorial institutionality, from what they are, do and feel as thinking and critical citizens of the reality in which they coexist, valuing the qualities that life in a territory represents, its environmental, biodiverse, inclusive and sustainable condition, in order to enable the mitigation and subsequent elimination of political, social and economic inequalities, for the shared benefit of those who are part of these habitable spaces.